The book of evidence - Achinstein, Peter (Oxford University Press, 2001)
What is required for something to be evidence for an hypothesis? In this text, Peter Achinstein, introduces here a basic concept of potential evidence which is characterised using a novel epistemic interpretation of probability.
Keywords: Evidence.; Évidence.; 08.35 philosophy of science.; PHILOSOPHY -- Epistemology.; Evidence; Bewijs (wetenschap); Evidentie.